In silico exploration of amyloid‐related imaging abnormalities in the gantenerumab open‐label extension trials using a semi‐mechanistic model. Issue 1 (6th June 2022) - Aldea, Roxana; Grimm, Hans Peter; Gieschke, Ronald; Hofmann, Carsten; Lott, Dominik; Bullain, Szofia; Delmar, Paul; Klein, Gregory; Lyons, Marco; Piazza, Fabrizio; Carare, Roxana O.; Mazer, Norman A.
Abstract: Introduction: Amyloid‐related imaging abnormalities with edema/effusion (ARIA‐E) are commonly observed with anti‐amyloid therapies in Alzheimer's disease. We developed a semi‐mechanistic, in silico model to understand the time course of ARIA‐E and its dose dependency. Methods: Dynamic and statistical analyses of data from 112 individuals that experienced ARIA‐E in the open‐label extension of SCarlet RoAD (a study of gantenerumab in participants with prodromal Alzheimer's disease) and Marguerite RoAD (as study of Gantenerumab in participants with mild Alzheimer's disease) studies were used for model building. Gantenerumab pharmacokinetics, local amyloid removal, disturbance and repair of the vascular wall, and ARIA‐E magnitude were represented in the novel vascular wall disturbance (VWD) model of ARIA‐E. Results: The modeled individual‐level profiles provided a good representation of the observed pharmacokinetics and time course of ARIA‐E magnitude. ARIA‐E dynamics were shown to depend on the interplay between drug‐mediated amyloid removal and intrinsic vascular repair processes. Discussion: Upon further refinement and validation, the VWD model could inform strategies for dosing and ARIA monitoring in individuals with an ARIA‐E history.